Engineered antibiotic nanoparticles for inhaled anti-biofilm therapy - Cheow, Wean Sin (2012)
Biofilm, a sessile community of bacterial cells that is enclosed by a self-secreted matrix composed of an extracellular polymeric substance, is implicated in the chronic pulmonary infection of patients with impaired lung mucociliary clearance mechanism, such as cystic fibrosis and chronic obstructive pulmonary disease (COPD) patients. The higher tolerance of biofilms to antimicrobial agents (10−1,000 fold less susceptible to antimicrobial agents compared to its planktonic counterparts) necessitates a targeted and controlled delivery of antibiotics. To this end, engineered antibiotics nanoparticles for inhaled anti-biofilm therapy via the dry powder inhaler (DPI) platform are investigated in this dissertation. First, in vitro investigations into the effects of antibiotic release profiles afforded by the encapsulation of antibiotics in nanoparticles on E. coli biofilm susceptibility shows that a biphasic extended release profile is necessary for maximum biofilm eradication. A high initial antibiotic concentration ensures that maximum biofilm cells were killed, while the subsequent slower extended release maintained an antibiotic concentration high enough to arrest biofilm proliferation. The initial maximum killing of biofilm cells is crucial as surviving biofilm cells are less susceptible to antibiotics. Second, lipid–polymer hybrid nanoparticles which combine the advantages of (i) the biofilm targeting ability of liposomes and (ii) the structural integrity and stability of polymeric nanoparticles, has been shown to result in higher antibiotic encapsulation efficiency compared to polymeric nanoparticles alone, hence are able to provide a higher initial antibiotic concentration. Furthermore, hybrid nanoparticles have been found to demonstrate higher in vitro efficacy against biofilm of P. aeruginosa compared to non-hybrid nanoparticles. For these reasons, lipid–polymer hybrid nanoparticles can be utilized as a vehicle for inhaled anti-biofilm therapy. However, the encapsulation of antibiotics in lipid–polymer hybrid nanoparticles must be tailored to the type of antibiotic and lipid used, as experiments performed show that ionic interactions between oppositely charged drug molecules and lipids prevent nanoparticle formation. Third, a new drug-polyelectrolyte nanoplexation method developed in the present work has resulted in antibiotic nanoparticles with high drug loading (up to 80%). The simple method, which only involves the mixing of two aqueous solutions of oppositely charged antibiotic and polyelectrolyte, has also been applied in the production of amorphous nanoparticles of a sparingly soluble antibiotic. The resultant amorphous antibiotic nanoparticle exhibits (i) faster dissolution rate, (ii) enhanced saturation solubility, and (iii) higher achievable supersaturation level compared to those of the raw crystalline drug. Finally, the engineered antibiotic nanoparticles can be transformed into inhalable dry powder nano-aggregates for pulmonary delivery by means of the spray drying or spray-freeze-drying (SFD) technique, both of which have been investigated in the present work. While the spray drying method to prepare dry powder nano-aggregates is more rapid and straightforward, the SFD is more suitable for the processing of thermosensitive nanoparticles due to the avoidance of a high operating temperature. Adjuvant selection in SFD is crucial as the adjuvant dictates the resulting nanoparticle-adjuvant structures, which in turn influence the aerodynamic diameter and aqueous re-dispersibility of the dry-powder aggregates.